Original articleImpact of rs12979860 polymorphism on liver morphology in chronic HCV infection - Łapiński, Tadeusz; Rogalska-Płonska, Magdalena; Panasiuk, Anatol; Kowalczuk, Oksana; Nikliński, Jacek; Flisiak, Robert (Clinical and Experimental Hepatology, 2015)
Aim of the study : To determine distribution of rs12979860 genotypes, their correlations with viral load as well as inflammatory activity and stage of liver fibrosis in patients infected with HCV genotype 1. Material and methods : The study included 132 patients infected with HCV genotype 1b. Serum viral loads were obtained with the PCR method. Rs12979860 polymorphisms were determined by sequencing of PCR products. Liver biopsy was performed in all patients. Results : CT, TT and CC alleles of rs12979860 polymorphism were detected in 58%, 20% and 22% of patients respectively. The highest viral load was observed in the TT and the lowest in the CC group (72.0 × 106 IU/ml vs. 2.1 × 10 6 IU/ml, p < 0.005). A significant correlation was demonstrated between patient’s age and inflammatory activity as well as degree of liver fibrosis. No association was found between liver histopathology and HCV viral load or rs12979860 genotypes. Conclusions : There is an association between HCV viral load and rs12979860 polymorphism. Inflammatory activity and stage of liver fibrosis depend on age, but there is no relationship with rs12979860 genotypes and HCV viral load.